NUTRISI TEPAT PADA PASIEN TALASEMIA - Sari, Meiriani; Fairuza, Firda; Setiati, Dita (Universitas Trisakti, 2024)
Thalassemia is one of the most common genetics disease in Indonesian children because Indonesia is located along the “Thalassemia Belt’. The disease usually occur in the early age, this condition reports many nutritional deficiencies in thalassemia patients. If not treated properly this condition may lead to growth and development impairments. Many parents and patients still not understand about what nutrition should be consumed. Although many of the parents and patients already understand about what nutrition should be consumed but they have not consumed it daily for some reasons. The seminar about the nutrition for thalassemia patients topic is seldom to be held. This is one of the reason why the knowledge about the appropriate nutrition for the patients is still not well understood. For that reason a discussion about appropriate nutrition for the thalassemia patients with thalassemia community , parents and thalassemia patients aimed to exposed them about the knowledge of which nutrition should be given, can be given or not to be given to thalassemia’s patients. In the end of the discussions we hope that the thalassemia’s family and patients can arrange the appropriate diet menu therefore the patients can get the appropriate diet daily. When the patients can get appropriate diet menu everyday we hope that their growth and development, health status and life quality will be well maintained. The knowledge about the appropriate diet of the thalassemia’s patients is very important. With the appropriate nutrition the thalassemia patient’s growth and development and quality of life can be well maintained.